2003
DOI: 10.1177/039139880302600113
|View full text |Cite
|
Sign up to set email alerts
|

Use of Octreotide to Treat Prolonged Sulfonylurea-induced Hypoglycemia in a Patient with Chronic Renal Failure

Abstract: A diabetic patient with chronic renal failure who developed recurrent and prolonged episodes of hypoglycemia associated with use of sulfonylurea agent is presented here. This patient was hospitalized with neuroglycopenic symptoms of hypoglycemia that persisted in spite of large doses of parenteral glucose replacement. On administration of somatostatin analogue octreotide, hypoglycemia resolved and, blood glucose levels were maintained even after cessation of parenteral glucose. The patient received 2 subcutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Sulfonylureas have been reported to cause hypoglycemia, increase in body weight, gastrointestinal (GI) disturbance, and headache to the user [19]. Besides, metformin could cause abdominal pain, diarrhea, nausea, and lactic acidosis to the diabetic patient [20]. In other diabetic drug that causes adverse side effects is thiazolidinediones as it causes hepatotoxicity after long-time usage [21].…”
Section: Introductionmentioning
confidence: 99%
“…Sulfonylureas have been reported to cause hypoglycemia, increase in body weight, gastrointestinal (GI) disturbance, and headache to the user [19]. Besides, metformin could cause abdominal pain, diarrhea, nausea, and lactic acidosis to the diabetic patient [20]. In other diabetic drug that causes adverse side effects is thiazolidinediones as it causes hepatotoxicity after long-time usage [21].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, octreotide has emerged as a viable therapeutic alternative. [5][6][7][8][9][10][11] Octreotide is a synthetic somatostatin analogue able to inhibit the release of a number of hormones, including insulin. After being injected subcutaneously, it acts within 20 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Patients have also been described with sulphonylurea induced HH who are refractory to treatment with boluses of dextrose but respond to octreotide. 189 Since the first reports, there have been numerous studies 190 217 describing treatment of sulphonylurea overdoses with octreotide. In virtually all the studies that reported the use of octreotide, there were no serious adverse effects.…”
Section: The Role Of Sst Analogues In Treatment Of Hhmentioning
confidence: 99%